Ózd humánerőforráshelyzetének változása a világgazdasági válságtól napjainkig = The changes in the human resource of Ózd after the global economic crisis - Káposzta, József; Nagy, Henrietta; Csehné Papp, Imola (Közép-Európai Közlemények, 2018)
Ózd is the centrum of an area in Hungary facing the most serious social and economic problems, where the multiple disadvantaged situation can be explained by the transferring and disappearing of certain factors. At present, Ózd and its surrounding area can be considered as external periphery, industrial crisis zone, disadvantaged area with high rate of Roma population that should be developed by complex programs. Though the number of employed increased in the past years, Ózd still belongs to the group of towns with high unemployment rate. It means especially serious social and economic problem that the rate of long-term unemployed and with low qualification is high among the young people entering the job market. In addition, the rate of employed in jobs with low prestige is also low. Based on the abovementioned, a question raises: what are the basic social factors in town that influence the development directions? In this study we intended to summarize the findings of the analysis of the abovementioned issues.